HISTORICAL INTERPRETATION OF RADEN KH SHOLEH DRAJAT’S AL-QUR’AN MUSHAF MANUSCRIPT THROUGH THE CODICOLOGICAL APPROACH - Zaidatul Awwaliyah, Mamlu’il; Faizah, Fatikhatul; Alwi HS, Muhammad; Hasanah, Nurul (Jurnal Lektur Keagamaan, 2023)
ABSTRACT This study aims to discuss the interpretation of history in Raden KH Sholeh Drajat’s Al-Qur’an ManuscriptinLamongan, East Java, focusing on the codicology aspect. The study was conductedby combining field research and literature study followingphilological theory based on a codicological approach.The results of this study indicated that thismanus-cript appeared in the village of Drajat, subdistrict of Paciran, Lamongan city in the 19thcentury, based on the type of the paper and the illumination. The paper was European paper with medallion watermark encrypted with Propatria. The scripts used mixed rasm and simple writing mechanics (without tajwidand mad). The use of floral illuminations in manuscripts shows that the manuscript was born with nuances of the archipelago. The writing of verses and pronunciations wasnot free from errors or corrupt texts, with classifications in the form of corrected errors, addition,and subtraction of pronunciations.This study strengthens the context-historical description of the manuscript, especially throughcodicological text analysis. Keywords: Quran Manuscript, Mushaf Raden KH. Sholeh Drajat, Codicology, Historical Interpretation.   ABSTRAK Studi ini bertujuan untuk membahas penafsiran sejarah dalam Naskah Al-Qur’an Raden KH Sholeh Drajat di Lamongan, Jawa Timur, dengan fokus pada aspek kodikologi. Kajian dilakukan dengan menggabungkan penelitian lapangan dan studi literatur mengikuti teori filologi berdasarkan pendekatan kodikologis. Hasil penelitian inimenunjukkan bahwa mushaf ini ditemukan di desa Drajat, kecamatan Paciran, kota Lamongan pada abad ke-19, berdasarkan jenis kertas dan penerangannya. Kertas itu adalah kertas Eropa dengan tanda air medali yang dienkripsi dengan Propatria. Aksaranya menggunakan rasm campuran dan mekanisme penulisan sederhana (tanpa tajwid dan mad). Penggunaan iluminasi bunga pada manuskrip menunjukkan bahwa manuskrip lahir dengan nuansa nusantara. Penulisan ayat dan lafalnya tidak lepas dari kesalahan atau korup teks, dengan klasifikasi berupa kesalahan koreksi, penambahan, dan pengurangan lafal. Kajian ini memperkuat deskripsi konteks-historis naskah, khususnya melalui analisis teks kodikologis. Kata Kunci: Manuskrip Al-Qur’an, Mushaf Al-Qur’an Raden KH. Sholeh, Kodikologi, Penafsiran Sejarah.